2001
DOI: 10.1093/clipsy.8.2.242
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating premenstrual dysphoric disorder from premenstrual exacerbations of other disorders: A methods dilemma.

Abstract: Premenstrual dysphoric disorder (PMDD) and premenstrual exacerbations of other disorders are difficult to distinguish. Previous methods, such as excluding women with other disorders from a PMDD diagnosis, do not enable a dual diagnosis. Our objective is to advance conceptual and clinical thinking and stimulate dialogue regarding this methods dilemma. The discussion sheds light on comorbidity in general, regardless of the disorders. Considering fundamental criteria for severe premenstrual disorders helps distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Although women with current psychiatric comorbidity or prior hospitalization for psychiatric disorders were excluded for the purposes of the trial from which the sample was included, women with a self-reported history of depression more frequently reported suicidal ideation. Notably, psychiatric comorbidity is not incompatible with the PMDD diagnosis if symptoms are unique in each disorder [ 9 ]. The exclusion of women with current psychiatric comorbidity may have led to an underestimation of the prevalence of suicidal ideation in women with PMDD in a real-world as opposed to a trial context.…”
Section: Discussionmentioning
confidence: 99%
“…Although women with current psychiatric comorbidity or prior hospitalization for psychiatric disorders were excluded for the purposes of the trial from which the sample was included, women with a self-reported history of depression more frequently reported suicidal ideation. Notably, psychiatric comorbidity is not incompatible with the PMDD diagnosis if symptoms are unique in each disorder [ 9 ]. The exclusion of women with current psychiatric comorbidity may have led to an underestimation of the prevalence of suicidal ideation in women with PMDD in a real-world as opposed to a trial context.…”
Section: Discussionmentioning
confidence: 99%
“…This is the third criterion. To ensure that symptoms of Premenstrual Dysphoric Disorder were not exacerbations of the symptoms of a woman's other ~sychiatric disorder(s), symptoms that overlapped with those of a woman's other existing psychiatric disorder(~) were excluded as ~ossible symptoms of her Premenstrual Dysphoric Disorder (Hartlage & Gehlert, 2001). This was done on a case by case basis.…”
Section: Methodsmentioning
confidence: 99%
“…The specific set of symptoms experienced by an individual woman may also vary from month to month (Halbreich, Endicott, & Nee, 1982). Many symptoms of Premenstrual Dysphoric Disorder, e.g., depressed mood, overlap with those of other psychiatric disorders, complicating the process of differentiating symptoms of Premenstrual Dysphoric Disorder from those of comorbid psychiatric disorders in women who have cornorbid disorders (Hartlage & Gehlert, 2001).…”
mentioning
confidence: 99%
“…It is important to recognize that neither PMDD nor PME are monolithic groups, and it is likely that some patients with PME are suffering from similar hormone sensitivities to those with prototypical PMDD and will therefore respond to similar treatments focused on reducing the negative effects of fluctuating hormones (see PMDD section above). While it is often the case that an individual has PMDD, PME, or neither, it is also possible to have both PMDD and PME (Hartlage & Gehlert, 2001). As an example, it is possible to have PME of depression (chronic depression with worsening before and during menses) and also have a PMDD pattern (i.e., luteal phase confinement) of five other symptoms-usually physical symptoms, mood swings, anger/irritability, rejection sensitivity, and anxiety symptoms that ONLY appear between ovulation and menses.…”
Section: Comorbidity and Overlap Between Pmdd And Pmementioning
confidence: 99%